Diseno de Hormigon Permeable Para el Aprovechamiento de Agua Lluvia en Superficies de Uso Peatonal (Global Journals of Research in Engineering, 2022)
In recent years we have seen the need to develop new methods or construction techniques that reduce the impact on our environment for this reason there is a constant search for organic products or at least sustainable alternatives Among the developments of sustainable construction is permeable concrete which allows the management of rainwater the same that infiltrates through this concrete Therefore in the present investigation we seek to focus on the design of a permeable transport system that provides water and that is not lost at the same time or to the water source Drinking water favoring the responsible management of the resource Permeable concrete being a non-structural concrete has low resistance to compression however the study complies with the necessary conditions to be used in pedestrian traffic zones with resistances that vary between 14 MPa and 18 MPa giving priority to the use of rainwater thus reducing the water demand of this limited natural resource worldwide The idea is to design a sustainable rainwater collection system which is technically and feasibly applied in places of light traffic becoming a feasible alternative to be used routinely
Keywords: permeable concrete (Pc)/water demand/water rain (Wr)/cement water relationship (W/C)